INTEGRASI LITERASI SAINS DAN HIGHER OTHER THINKING SKILL (HOTS) DALAM PEMBELAJARAN IPA SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS VII SMP FUTURE ISLAMIC SCHOOL PEKANBARU - Gustriani, Riah; Suryawati, Evi; Suwondo, Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The main issue brought up in this research is that low achievement of student’s learning in school is caused by their lack of interest in reading textbooks along with their poor ability in analyze and solve the problems given in form of tests or questions which require them to think in highly level. This is a Classroom Measure Research which aims to improve science learning result of 7th grade students of Future Islamic Junior High School Pekanbaru by integrating science literacy and Higher Other Thinking Skill (HOTS) in learning science. This research was conducted from March to April 2018. A total of 23 students of 7th grade (15 boys and 8 girls) contributed as subject of this research. Data collecting using test method and non-test method. Research procedure has been done through two cycles started with plan, execution, action, observation phase and finished with final phase. Parameter in this research is student’s learning result. The result shows that psychomotor aspect was at 76,87 (C) for cycle I become 83,98 (C) on cycle II. Meanwhile, for affective aspect, the score changed from 2,74 (B-) on cycle I to 2,85 (B) on cycle II. cognitive score was changing as well from 75,21 (C) on cycle I to 77,39 (C) on cycle II. The percentage of student’s learning from 60.86% in the first cycle to 65.21% in cycle II. It can be concluded from the result that integrating science literacy and HOTS in learning science can improve the learning result of 7th grade students of Future Islamic Junior High School Pekanbaru.Keywords: Science Literacy, Higher Other Thinking Skill, Learning Result